Stability of compactification during inflation - Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 1990)
The possibility that inflation may trigger an instability in compactification of extra spatial dimensions is considered. In old, new, or extended inflation, the false-vacuum energy results in a semiclassical instability in which the scalar field representing the radius of the extra dimensions may tunnel through a potential barrier leading to an expansion of the internal space. In chaotic inflation, if the initial value of the scalar field responsible for inflation is large enough, the internal space becomes classically unstable to ever increasing expansion. Restrictions on inflationary models necessary to keep the extra dimensions small are discussed.
Gesehen am 22.11.2017